High-temperature performance in Al2O3–Cr2O3 refractories: Effect of Al2TiO5. Issue 3 (1st February 2022) - Wang, Yuze; Zhao, Huizhong; Zhang, Han; Gan, Cunqiang; Hu, Deng; Zhao, Pengda; Zhao, Yang; Huang, Bo
Abstract: In an effort to reduce resource consumption through recycling, Al2 O3 –Cr2 O3 refractories were prepared by sintering a mixture of brown corundum and recycled aluminum chromium slag at 1600 °C. To elucidate the significance of TiO2 in refractory, the effect of TiO2 addition on the room- and high-temperature mechanical properties of these refractories was investigated. The observed stepwise progression in the high-temperature mechanical properties of the specimens was explained by considering the results of thermodynamic simulations, as well as those of phase and microstructural analyses. This behavior was ascribed to the generation of Al2 TiO5 in the matrix of the specimens. Moreover, the addition of TiO2 increased the content of undecomposed Al2 TiO5, and it was accompanied by the appearance of several microcracks in the matrix portion. The high temperatures caused the integration of microcracks and counteracted the thermal stresses in the specimens, which considerably improved the high-temperature mechanical properties and the thermal shock resistance.